La muqueuse buccale - Edgard NEHMÉ (International Arab Journal of Dentistry (IAJD), 2010)
Title: “The Oral Mucosa, From the Clinic to the Treatment”Authors: Roger KUFFER, Tomasso LOMBARDI, Corinne HUSSONBUI, Bruno COURRIER, Jacky SAMSON.Editor MED’COM, Paris, 2009